Decrypting Catalytic NOx Activation and Poison Fragmentation Routes Boosted by Mono- and Bi-Dentate Surface SO32-/SO42- Modifiers under a SO2-Containing Flue Gas Stream - Kim, Jongsik; KIM, DONG HO; Park, Jinseon; Jeong, Keunhong; Ha, Heon Phil (American Chemical Society, 2022)
SOA2- (A = 3-4; B-) functionalities are anchored on metal oxides used to catalyze NH3-assisted selective NOx reduction (SCR) for a SO2-bearing feed gas stream. SO(A)(2-)species act as conjugate bases of Bronsted acidic bonds (B--H+) and modifiers of redox sites (M(n-1)+-O-), both of which are combined to dictate the activities of SCR (-r(NOX)) and ammonium (bi) sulfate (AS/ABS) poison degradation (-r(AS/)(ABS)) at low temperatures. Nonetheless, their pathways have been barely clarified and underexplored, while questioning catalytic significance of mono-dentate or bi-dentate SOA2- species in dominating -r(NOX) and -r(AS/ABS). While using Sb-promoted MnV2O6 as a reservoir of SOA2- functionalities with distinct binding arrays, elementary stages for the SCR and AS/ABS degradation were proposed, thermodynamically assessed, and analyzed using kinetic control runs in tandem with density functional theory calculations. These allowed for the conclusions that the reaction stage between B--H+center dot center dot center dot NH3 center dot center dot center dot O--M(n-1)+ and gaseous NO and the liberation stage of H2O/SO2 from B-center dot center dot center dot H2O center dot center dot center dot SO2 center dot center dot center dot H2O via dissociative desorption are endothermic and dominate -r(NOX) and -r(AS)(/)(ABs) as the rate-determining steps of the SCR and AS/ABS degradation, respectively. In addition, mono-dentate and bi-dentate SOA2- species are verified central in directing -r(NOX) and -r(AS/ABS) by elevating collision frequency between B--H+center dot center dot center dot NH3 center dot center dot center dot O--M(n-1)+ and NO and declining the energy barrier required for dissociative H2O/SO2 desorption for the SCR and AS/ABS degradation, respectively. In particular, mono-dentate SOA2- functionalities can improve the overall redox trait of the surface, thereby substantially promoting its low-temperature SCR performance under a SO2-excluding feed gas stream. Meanwhile, bi-dentate SOA2- functionalities can slightly improve the overall redox trait of the surface, yet, can readily degrade AS/ABS by accelerating the endothermic fragmentation of S2O72- innate to ammonium pyrosulfate, while compensating for the moderate efficiency in fragmenting NH4+ of ammonium pyrosulfate via Eley-Rideal-type SCR This can significantly elevate the SCR performance of the bi-dentate SOA2--containing surface under a SO2-including feed gas stream alongside with the promotion of its long-term stability at low temperatures. These can be adaptable and exploited in discovering/amending a host of metal oxides (or vanadates) imperatively functionalized with SOA2- or poisoned with AS/ABS under low thermal energies.